Theoretical-Epistemological Reflexivity: A Review of Praxis and Logic in Teacher Training (Orinoquia, 2019)
This article presents the results of a research about theoretical and epistemological perspectives in pedagogical practices of graduates from the Early Childhood Pedagogy program at Universidad de los Llanos, which raised as objective, to understand the relationship between teaching practices and theoretical and epistemological perspectives consolidated in the cycle of undergraduate training of the teachers graduated from the Early Childhood Pedagogy program at Universidad de los Llanos. The study took the Diatopic hermeneutics as a methodology that allowed researchers, graduates and students práctito re-know and understand themselves as contextualized body subjects, who have knowledge and know-how in the framework of Theoretical-epistemological postures. The conclusions allow to demonstrate that in the institutional and formative/formed narratives, some significant coherences are set, but the distortions between the same ones prevail and it shows up a complex theoretical-practical relationship.
Keywords: reflexivity; theoretical-epistemological perspectives; teaching practice